폐 평활근종 치험 1례 - 홍기표 (Taehan Hyungbu Oekwa Hakhoe chi, 1993)
We have experienced a case of leiomyoma in the right upper lobe of the lung in a 56 year old female. Preoperative studies revealed the tumor nature as benign, and we chose right upper lobectomywith video-assisted thoracoscope rather than with the usual posterolateral thoracotomy. Postoperativehistological diagnosis was pulmonary leiomyoma which is a rare type of benign lung tumor.